PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN DIGITAL UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS KELAS IV SD NEGERI KALIKALONG - Muhammad Ferdian Syaifullah; Tanti Trinawati; Ratri Nur Fauziah (Dharmas Education Journal (DE_Journal), 2026)
Learning problems at Kalikalong State Elementary School show that students are still less focused on learning because the material delivered is still lectures and students cannot think abstractly, so the solution to this problem is by developing learning media. The purpose of this study is 1) to find out the development of learning media; 2) to find out the feasibility of developing learning media that includes validity, practicality, and effectiveness. The method in this study is the R&D method with the ADDIE model. The media developed is a digital game media from the Canva platform. The game developed contains the Science material "My Residential Area". The application of this media is by conducting limited tests and extensive tests on 14 fourth grade students of Kalikalong State Elementary School. The results of this study show 1) The ADDIE paradigm, which has five stages of analysis, design, development, implementation, and evaluation is the basis for the needs and models for developing digital game learning media; 2) the validity of the development of learning media is classified as very valid from the results of material experts, media experts, and practitioners with an average score of 3.58 on a scale of 4; 3) practicality is classified as very practical from the results of broad and limited student responses resulting in a percentage of 94.7%; and 4) effectiveness is classified as very effective obtained from the results of the pretest value of 68.6 and the results of the posttest value of 87.1 which shows an increase in value.